Strengthening Regional Security Through The Establishment Of The Asean Counter Terrorism And Peacekeeping Task Force Led By Indonesia In Collaboration With The United States - Yulian Tri Saptono; I Gede Sumertha; Halomoan Freddy Sitinjak Alexandra; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
In recent years, the Southeast Asian region has witnessed an increase in terrorism threats, posing significant challenges to its security and stability. To address this pressing issue, the Association of Southeast Asian Nations (ASEAN) has taken a proactive approach by establishing the ASEAN Counter Terrorism and Peacekeeping Task Force. This research aims to explore the formation of this task force, with a specific focus on Indonesia's key role in cooperation with the United States, and assess its impact on strengthening regional security. The main objective of this research is to examine the reasons behind the establishment of the ASEAN Counter Terrorism and Peacekeeping Task Force and understand the factors that underlie Indonesia's selection as the leading sector. Using qualitative research methods, this study seeks to gather insights into the motivations, strategies, and goals of this collaborative effort. The research findings will elucidate the importance of the ASEAN Counter Terrorism and Peacekeeping Task Force, where Indonesia plays a crucial role as the leading sector in maintaining regional security stability in ASEAN, collaborating with the United States. Through close partnership with the United States, Indonesia has the potential to become the leading sector in the ASEAN Counter Terrorism and Peacekeeping Task Force.